(untitled) (Bangladesh Journal of Medical Science, 2013)
Foreign body aspiration often occurs amongst extreme age. Most of aspirated object are; nuts, nails, pins, coins, metal piece and dental appliances. Foreign body aspiration can be life threatening. Patients with foreign body aspiration may present with choking, coughing, wheezing, haemoptysis, asphyxia and even death. The symptoms and severity depend on the site of obstruction. This is a case of 9 year old boy provided the history of aspiration of white board needle. He had persistent cough but examination revealed normal vital signs. Radiological examination confirmed needle like radio opaque material in his trachea. This case report depicts the management and bronchoscope as diagnostic procedure of this case and role of X-ray and CT scan in dealing with foreign body in the tracheobronchial tree. DOI: http://dx.doi.org/10.3329/bjms.v12i4.16668 Bangladesh Journal of Medical Science Vol. 12 No. 04 October 13 Page 449-452